(untitled) (Cadernos de Sociomuseologia, 2018)
The importance of education (which is not only that one of curricula and power) and of cultural heritage (which belongs to communities) has not succumbed to the overthrow and change of paradigm from a solid society to a liquid one, as Bauman reminds us, like those who for years have made education and heritage their struggle and their policy of intervention, patented in multiple anonymous, private and silent (or silenced) projects. The current times show that this intervention - which unites education and cultural heritage - contains a sensitivity, a poetics, an art, a policy, for returning education to the heart of emancipation and cultural heritage to communities, is a form of citizenship intervention, social development and the power of self-determination. Keywords: Education, heritage, citizenship, development, interculturality, cultural entrepreneurship.